Pengaruh Motivasi Karir Dan Peningkatan Kualitas Diri Terhadap Minat Mahasiswa Mengikuti Sertifikasi Brevet Pajak A Dan B (Studi Empiris Mahasiswa Akuntansi Universitas Islam Malang Dan Universitas Negeri Malang) - Giyanti Ratna Sari; Noor Shodiq Askandar; Abdul Wahid Mahsuni (Universitas Islam Malang, 2023)
This study discusses the influence of career motivation and self-quality improvement onstudents interest in participating in the A and B brevet certifications. Data types in this studyare quantitative. The sampling method used is to use the slovin formula with the data collectionmethod using a questionnaire through google form. The population in this study is studentswho have taken taxation courses at the Faculty of Economics and Business, Islamic Universityof Malang and State University of Malang as many as 389 students.The results of this study indicate that partially career motivation affects student interestin participating in A and B tax brevet certification. As well as improving self-quality, it affectsstudents interest in participating in the A and B tax brevet certification. Meanwhile,simultaneously the two variables, namely career motivation and self-quality improvement,have a significant effect on the level of students participating in the A and B tax brevetcertification.Keywords: Career motivation, self-improvement, student interest in participating in the a andb tax brevet certification.